Aging-- the methuselah syndrome - WGBH (Television station : Boston, Mass.) ([New York, N.Y.] : Time Life Video, 1982)
A startling report on research which is making giant strides toward pinpointing the body controls that cause aging--and could some day transform the world by finding a real Fountain of Youth.
Don Wescott.
Keywords: Aging; Gerontology